2021
DOI: 10.3390/biology10040292
|View full text |Cite
|
Sign up to set email alerts
|

A Uremic Goat Model Created by Subtotal Renal Artery Embolization and Gentamicin

Abstract: A large animal model of (end-stage) kidney disease (ESKD) is needed for the preclinical testing of novel renal replacement therapies. This study aimed to create stable uremia via subtotal renal artery embolization in goats and induce a temporary further decline in kidney function by administration of gentamicin. Renal artery embolization was performed in five Dutch white goats by infusing polyvinyl alcohol particles in branches of the renal artery, aiming for the embolization of ~80% of one kidney and complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…We observed a distinct baseline level of plasma IS concentration among different species, but these levels are comparable to previously reported studies with human (Imazu et al, 2020 ; Poesen et al, 2015 ), goat (van Gelder et al, 2021 ), rat (Aoyama et al, 2002 ; Kikuchi et al, 2010 ), and mouse (Hung et al, 2016 ; Mishima et al, 2018 ). IS concentration in pig plasma has not been reported earlier.…”
Section: Discussionsupporting
confidence: 91%
“…We observed a distinct baseline level of plasma IS concentration among different species, but these levels are comparable to previously reported studies with human (Imazu et al, 2020 ; Poesen et al, 2015 ), goat (van Gelder et al, 2021 ), rat (Aoyama et al, 2002 ; Kikuchi et al, 2010 ), and mouse (Hung et al, 2016 ; Mishima et al, 2018 ). IS concentration in pig plasma has not been reported earlier.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a similar endovascular nephrectomy protocol has been used to induce uremia in swine for the study of novel peritoneal dialysis therapies [ 22 ]. The same group has also developed an acute-on-chronic goat model of kidney injury using a combination of endovascular nephrectomy and gentamicin-induced kidney injury with animals surviving for 10 months; a procedure which may be advantageous for studying chronic dialysis therapies [ 23 ]. In our protocol, we found that a staged approach results in a state of renal failure manageable with initial daily hemodialysis for one week, followed by hemodialysis every 2–3 days, and allows the animals to stay healthy for at least one month (see Table 1 for detailed comparison of the surgical approaches).…”
Section: Discussionmentioning
confidence: 99%
“…An ideal model should replicate human renal physiology and anatomy, induce stable renal failure while remaining compatible with standard hemodialysis techniques, and preserve surgical anatomy for implantation of experimental RRT devices. Animal models with some of these characteristics have been established in swine, sheep, and goats [ 21 , 22 , 23 , 24 ]. Specifically in swine, several models have been developed to induce acute and chronic renal failure via surgery, ischemia-reperfusion (IR) injury, sepsis, nephrotoxic drugs, and combinations these modalities.…”
Section: Introductionmentioning
confidence: 99%